Power consumption modeling for indoor environment using artificial neural network - Rahman, A. F. A. (2013)
In this paper, a new Artificial Neural Network (ANN) model that relates human comfort and electrical power consumption of a building with temperature, illumination and carbon dioxide (CO2) level inside the building is developed. The model has been developed using samples of simulated data representing the indoor environment variables. Results have shown that neural network with 14 hidden layer neurons produces outputs that is closest to the actual system outputs.